Pyrolysis of Refuse Derived Fuel (RDF) / Raja Razuan Raja Deris, Changkook Ryu and V. N. Sharifi - Raja Deris, Raja Razuan; Ryu, Changkook; V. N., Sharifi (2006)
Refuse Derived Fuel (RDF) was pyrolysed at temperature ranges from 300°C to 800°C with heating rate of 10°C/min. The char yield decreased with increasing pyrolysis temperature up to 500°C, from 68.19% to 36.76% Above 500°C the char yield was almost constant. However, the gas yield (includes the loss of fine oil droplets) shows an opposite trend, with increasing pyrolysis temperature. The oil production was almost stable above temperature 500°C. Liquid yield was very low which was below temperature 400°C because of the temperature was not sufficient enough for the RDF to pyrolyse. However, at temperature above 400°C, most of the oil produced has broken to yield more gas product. The analysis of pyrolysis gas showed that CO and CO2 are dominant in the early stage of pyrolysis. Hydrocarbon, H2 starts to appear at temperature above 500°C.